THE PERFORMATIVE ACTS AND THE CONSTRUCTION OF EVENTS IN PERFORMANCE - Suárez, Andrés Felipe Restrepo [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
The objective of this article is to study philosophical theories about “performative statements” and the artworks Leap into the void by Yves Klein and Action Pants: Genital Panic by VALIE EXPORT, analyzing distinct forms by which the events are triggered in the performance. According to the theories about performative utterances proposed by John Austin and Jacques Derrida, the artist has the power to define the real through his visual and dialectical discourses, in which the action is structured from a previously constructed documentation, understood as real and legitimate by the institution of art. Just like it is evidenced in the artworks of Klein and EXPORT through the diffuse transit of a simulated performance and a performance held in an agora.
LOS ACTOS PERFORMATIVOS Y LA CONSTRUCCIÓN DE LOS ACONTECIMIENTOS EN LA PERFORMANCE
OS ATOS PERFORMATIVOS E A CONSTRUÇÃO DOS ACONTECIMENTOS NA PERFORMANCE
Keywords: Action; Event; Performance; Performative Utterances; Simulation